Improved effect of deep eutectic solvents on polymeric film of surfactant: application in determination and discrimination of dihydroxybenzene isomers as model molecules. (10th October 2018) - Dorraji, Parisa Seyed; Fotouhi, Lida
Abstract : The simultaneous determination of hydroquinone and catechol with different deep eutectic solvents (DESs) employed in the polymerization step of cetyltrimethylammonium bromide (CTAB) on an oxidized glassy carbon electrode is studied. Abstract : The simultaneous determination of hydroquinone and catechol with different deep eutectic solvents (DESs) employed in the polymerization step of cetyltrimethylammonium bromide (CTAB) on an oxidized glassy carbon electrode is studied. Applying DESs in the polymerization step of CTAB significantly increased the currents of hydroquinone and catechol. The catalytic efficiency of the DESs is in the order of choline chloride–urea > choline chloride–citric acid > choline chloride–ethylene glycol.